Posttraumatic Arteriovenous Fistula of the Distal Posterior Tibial Artery as Cause of Delayed Wound Healing in an Unrecognized Arterial Injury - Roth, Peter; Heiss, Christian; Koshty, Ahmed; Niemann, Bernd; Boening, Andreas (The Thoracic and Cardiovascular Surgeon Reports, 2014)
Background Cases of posttraumatic arteriovenous (AV) fistula of the distal lower limb are rarely reported. Time from trauma to diagnosis varies from hours to years.Case Description This case report of a 51-year-old male patient shows very impressively the extensive consequences of an unrecognized traumatic AV fistula. The fistula developed here after a car accident led to a massive healing delay in a pilon fracture of the tibia and a wound, resulting in almost 1 year immobilization, 20 operations, and extensive pain drug therapy. After surgical revision of the fistula, bone and wound healing improved quickly.Conclusions The possibility of an AV fistula should be considered in case of persistent swelling after high-energy trauma of an extremity. The therapy of choice is surgery and the long-term result of successful fistula ligature is excellent.
Keywords: artery/arteries; wound healing; trauma